Hydrogeochemistry of Two Major Mid-hill Lentic Water Bodies for Irrigation of the Central Himalaya, Nepal - Babi Kumar Kafle; Chhatra Mani Sharma; Smriti Gurung; Nani Raut; Kumud Raj Kafle; Rita Bhatta; Lekhendra Tripathee; Rukumesh Paudyal; Junming Guo; Shichang Kang; Bed Mani Dahal (Environment and Natural Resources Journal, 2023)
The concentration and composition of different salts in natural water bodies determine the water quality for various purposes. This study assesses the water quality of two mid-mountain lentic water bodies, Lake Phewa and Kulekhani Reservoir. For this purpose, selected physico-chemical parameters along with major ions such as HCO3-, SO42-, PO43-, NO3-, Cl-, Ca2+, Mg2+, Na+, K+, and NH4+ were analyzed. Major ions were analyzed using ion chromatography, anions by DX-600 and cations by Dionex ISC-2500 ion chromatographs. The sources of major ions were determined by using the Gibbs diagram, Piper plot, and Scatter plots. Dissolved oxygen, ammonia and phosphate showed seasonal variations in both lakes. The concentrations of cations are in the order of Ca2+ > Na+ > Mg2+ > K+ in both water bodies. However the trend of anions had small variations for Cl- and SO42- in Lake Phewa (HCO3- > Cl- > SO42- > NO3-) and Kulekhani Reservoir (HCO3- > SO42- > Cl- > NO3-). The Piper plot and equiline plots indicated that the water chemistry is dominantly controlled by the dissolution of carbonate minerals and to a limited extent by weathering of silicate minerals. This is further supported by the Gibbs plot showing bedrock geology as the main source of major ions. The overall study indicates that the hydrogeochemistry of these water bodies is controlled by local geology and is suitable for irrigation purposes.